2018
DOI: 10.1007/s13224-018-1176-7
|View full text |Cite
|
Sign up to set email alerts
|

Irisin as a Novel Marker for Insulin Resistance in Iraqi Women with Polycystic Ovary Syndrome Before and After Metformin Therapy

Abstract: Background Polycystic ovarian syndrome affects 5-10% of women; it represents the most common cause of hyperinsulinemia with anovulation. Many biomarkers are used to assess insulin resistance. Irisin is a newly discovered myokine associated with insulin resistance and other metabolic syndromes.Objective To measure the serum level of irisin in polycystic ovary syndrome patients and assess the effect of metformin treatment on its level. Method This study was a prospective interventional study conducted in a priva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…Considering the association between obesity and irisin levels, Chang et al (24) found higher serum irisin levels in overweight women (BMI higher than 25 kg/m 2 ), independent of their PCOS status, and in overweight PCOS patients from China. Similar ndings have been reported by the other authors (25). In light of these ndings, it has been thought that the brown adipose-differentiation factor irisin might represent a potential biomarker for PCOS, increase the diagnostic accuracy for PCOS, and might be used to improve the metabolic disorder of PCOS (7,8,22,24).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Considering the association between obesity and irisin levels, Chang et al (24) found higher serum irisin levels in overweight women (BMI higher than 25 kg/m 2 ), independent of their PCOS status, and in overweight PCOS patients from China. Similar ndings have been reported by the other authors (25). In light of these ndings, it has been thought that the brown adipose-differentiation factor irisin might represent a potential biomarker for PCOS, increase the diagnostic accuracy for PCOS, and might be used to improve the metabolic disorder of PCOS (7,8,22,24).…”
Section: Discussionsupporting
confidence: 87%
“…The impact of PCOS on serum irisin levels has been studied previously. Several authors showed higher irisin levels in PCOS women than healthy women (11,(22)(23)(24)(25). They also reported higher irisin levels associated with hyperandrogenic PCOS (23).…”
Section: Discussionmentioning
confidence: 99%
“…As like previous report in our study population also we did not observe fasting glucose level in diabetic range(70-100 mg/dL normal range of fasting glucose).however when we calculated HOMA-IR which combines the fasting glucose and insulin level, it showed relative insulin resistance (>3) in both obese and non obese PCOS as well as in obese healthy control. As irisin is functionallyrelated to increase insulin sensitivity 19,20 , the observation of relative insulin resistance in obese and non obese PCOS group is consistent with the observation of low irisin level in PCOS.…”
Section: Discussionsupporting
confidence: 86%